Selection of maize genotypes resistant to grey leaf spot (Cercospora zeaemaydis) - Acharya, B; Regmi, H; Khadka, RB; Rijal, TR (Journal of Agriculture and Environment, 2018)
Gray leaf spot (GLS), caused by Cercospora zeae-maydis is an important and destructive foliar disease of maize (Zeae mays) mostly in the mid hills of Nepal. Considering its potential threat to maize production, a total of fourty two and thirty different maize genotypes were evaluated in the year 2012 and 2013 respectively with two replications in observation nursery at Kapurkot, Salyan (1480 masl) for resistance to GLS. Disease assessment was made using 1-5 scale at 15 days interval for three times starting from tasseling stage (65 days after sowing). The results showed that no immune and highly resistant genotypes were found in both the year. Response of 27 out of 42 genotypes of maize were identified as moderately resistant (2-2.5 score) and 15 genotypes showed moderately susceptible (3 score) to GLS during 2012. During 2013 out of 30 genotypes of maize 27 were identified as moderately resistant (1.75-2.5 score) and 3 moderately susceptible (2.75-3 score) to GLS. Among the tested genotypes, BGBYPOP, Rampur SO3FO4, Celaya OOHGYA*HGYB, O7SADVI, Manakamana-3, SO1SIYQ and local were found most promising and moderately resistant to GLS disease during 2012 and SYN312-SR and CML-395/CML-444 during 2013.